Distribución de alelos de los genes DRD4 y DAT1 del sistema dopaminérgico en la población mixta de Santiago de Chile - Vieyra S,Gonzalo (Sociedad Médica de Santiago, 2003)
Genes for dopamine receptor DRD4 and dopamine transporter DAT1 are highly polymorphic. Two alleles of these genes, namely the DRD4.7 and the DAT1*9 are frequently associated to the attention deficit disorder with hyperactivity. In Europe, the allele for DRD4 receptor with four repetitions (DRD4.4) has the highest frequency, with a median of 69%, followed by DRD4.7, with a frequency of 15%. South American indigenous populations have higher frequencies for DRD4.7 (61%) than for DRD4.4 (29%). The ten repetition allele for DAT1 transporter has a high frequency among Europeans (72%) and Amerindians (100%). The allele DAT1*9 is the second most frequent allele. Aim: To study the frequency of DRD4 and DAT1 alleles in a Chilean population sample. Material and methods: One hundred serum samples were obtained from blood donors in two public hospitals in Santiago. Polymorphic regions for DRD4 and DAT1 were amplified by polymerase chain reaction. Results: The allele DRD4.4 had a frequency of 59% and DRD4.7 a frequency of 27%. The allele DAT1*10 had a frequency of 74%, followed by DAT 1*9, with a frequency of 23%. Discussion: In a Chilean population sample, the frequency of DRD4 and DAT1 alleles was very similar to that of European populations (Rev Méd Chile 2003; 131: 135-43)